Sistem Pakar Konsultasi Penyakit Kulit Dengan Metode Forward Chaining Pada Klinik Medika - Andy Dharmalau; Jamah Sari; Septiana Ningtyas; Indra Hiswara (STMIK Sinar Nusantara, 2023)
Expert systems have information gained through a combination of readings, training, and practical experience. As a result, professionals can make faster and more accurate decisions while tackling complicated situations than non-experts. Klinik Medika is a health-care organization that focuses on public health, particularly skin health issues. This clinic's services to patients for consultation and treatment need to be improved in terms of service time efficiency. For this reason, an expert system is required so that patients can consult online rather than visiting the clinic.The goal of this research is to apply Forward Chaining method to create an expert system that can be used to consult on various skin conditions. Based on the results of the tests, the expert system can correctly diagnose the signs of skin disorders with a 90% accuracy. The system can also accept errors caused by differences in knowledge based on computational data and the experience of skin disease experts.